Students’ cognitive and metacognitive learning strategies towards hands-on science - Leslie Gomez Discipulo; Romiro Gordo Bautista (Institute of Advanced Engineering and Science, 2022)
Cognitive and metacognitive learning strategies are geared towards giving autonomy to every learner in their studies. Students’ affordances on cognitive and metacognitive learning strategies in their studies are believed to predict their academic success and performances in their learning tasks. This study determined the cognitive and metacognitive learning strategies in science among the 278 education students in the three campuses of a state university in the Philippines as bases in crafting a developmental plan to bolster the science instruction in the university. Using the descriptive-inferential research and employing a questionnaire on the cognitive and metacognitive strategies of education students, the following are known: incomparable affordances of the students along planning and information management practices while comparable affordances were determined on the respondents’ cognitive learning strategies; and incomparable affordances along procedural knowledge while comparable affordances along declarative and conditional knowledge were determined on the respondents’ metacognitive learning strategies. Based on the results, a developmental plan was designed to bolster the science courses in the education programs of the university centering on the inclusion of research camp, research expo, shepherding on research through the niche program, immersion, and hands-on science. It was recommended that the proposed enhanced science program will be implemented in the university system as there is only one science course in their respective programs in the new curricular plot.